PENGARUH KEPEMIMPINAN, BUDAYA ORGANISASI, DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA KANTOR DIREKSI PT PERKEBUNAN NUSANTARA XIV MAKASSAR - Ilham Safar (Jurnal Bisnis dan Kewirausahaan, 2018)
The purpose of research is 1) to analyze the influence of leadership on employee performance of PT Perkebunan Nusantara XIV directors office, 2) to analyze the influence of organizational culture on employee performance of PT Perkebunan Nusantara XIV directors office, 3) to analyze the influence of work environment on employee performance of PT Perkebunan Nusantara XIV. The method of analysis used in this study is the method of multiple regressions analysis. The research data was obtained from employees of PT Perkebunan Nusantara XIV office. The research approach is a causal approach that is explanatory. The results of this study indicate that: 1) regression results indicate that leadership variables have a positive and significant impact on employee performance of directors of PT Perkebunan Nusantara XIV. This shows that leadership has an important role in improving employee performance as well as execution of duties within a company. 2) regression result indicate that organizational culture variable have positive and significant effect to employee performance of PT Perkebunan Nusantara XIV directors office. This suggests that a good and targeted organizational culture will have a positive impact on companies especially on improving employee performance. 3) regression result indicate that work environment variable have positive and significant effect to employee performance of PT Perkebunan Nusantara XIV directors office. This shows that a healthy working environment, comfortable and support activities of worship will have a positive impact for employees in improving its performance for the company.